Nano‐TiO2 penetration of oral mucosa: in vitro analysis using 3D organotypic human buccal mucosa models. (8th July 2016) - Konstantinova, Victoria; Ibrahim, Mohamed; Lie, Stein A.; Birkeland, Eivind Salmorin; Neppelberg, Evelyn; Marthinussen, Mihaela Cuida; Costea, Daniela Elena; Cimpan, Mihaela R.
Abstract : Background: Oral cavity is a doorway for a variety of products containing titanium dioxide (TiO2 ) nanoparticles (NPs) (nano‐TiO2 ) such as food additives, oral healthcare products and dental materials. Their potential to penetrate and affect normal human oral mucosa is not yet determined. Objectives: To evaluate the ability of nano‐TiO2 to penetrate the in vitro reconstructed normal human buccal mucosa (RNHBM). Methods: RNHBM was generated from primary normal human oral keratinocytes and fibroblasts isolated from buccal oral mucosa of healthy patients ( n = 6). The reconstructed tissues were exposed after 10 days to clinically relevant concentrations of spherical or spindle rutile nano‐TiO2 in suspension for short (20 min) and longer time (24 h). Ultrahigh‐resolution imaging (URI) microscopy (CytoViva ™, Auburn, AL, USA) was used to assess the depth of penetration into reconstructed tissues. Results: Ultrahigh‐resolution imaging microscopy demonstrated the presence of nano‐TiO2 mostly in the epithelium of RNHBM at both 20 min and 24‐h exposure, and this was shape and doze dependent at 24 h of exposure. The depth of penetration diminished in time at higher concentrations. The exposed epithelium showed increased desquamation but preserved thickness. Conclusion: Nano‐TiO2 is able to penetrate RNHBM and to activate its barrier function in a doze‐ and time‐dependent manner.